Inconsistência e racionalidade : uma introdução ao paradoxo do prefácio - Rodrigues, Lucas Roisenberg (2012)
The dissertation aims to explain the so called Preface Paradox , and also evaluate some of the main solutions found in the literature about it. The Preface Paradox is a situation in which somebody has some set of seemingly rational inconsistent beliefs. Because consistency is considered a fundamental condition of rationality, the paradox has received some attention from the philosophical community, since it was first brought to public knowledge. I also try to show that the paradox can be generalized, and that it points at a important and hard problem